Ratio Likuiditas, Solvabilitas dan Rentabilitas Pada PT. Hanita Transindo Utama Semarang - Artanti, Artanti; Kurnianingsih, Heny (STIE Surakarta, 2013)
Company Financial Ratio describe company condition.Soo from this the company will be take decision. Rentability, Solvability, Liquidity ratio this research to result that company condition all be fine. Company can give short term and long term liability. The Company has been liquid, solvable, rendabel. Liquidity ratio is not too hight. This to prove the company capable use the founds is efficient.